The Effect Of Corporate Social Responsibility Disclosure, Independent Commissioner, Audit Committee And Company Size On Tax Aggressiveness - Yolanda Pratami; Ricardo Manerak Manumpak Simamora (UNIB Press, 2024)
This study aims to examine and analyze the influence of Corporate Social Responsibility Disclosure; independent commissioner; audit committee; and company size on Tax Aggressiveness in mining companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The population in this study is 53 mining sector companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The research sample was selected using a purposive sampling technique in order to obtain 15 companies that met the research criteria during the 2020-2022 timeframe. Data analysis used multiple linear regression analysis techniques. Data were analyzed using SPSS version 23. Based on the results of the tests that have been carried out, it shows that the Corporate Social Responsibility variable, the independent commissioner and the audit committee has no significant effect on tax aggressiveness. The company size variable has a positive effect on tax aggressiveness. Simultaneously the variables of corporate social responsibility, independent commissioners, audit committees and company size have no significant effect on tax aggressiveness. The weakness of this research is the limitation of the use of research variables. Moreover, researchers only use research objects in specific sectors for a limited period of time, i.e. for 3 years.